Bone Marrow Disseminated Tumor Cell Detection Is Beneficial for the Early Finding of Bone Metastasis and Prognosis - Yulan Wang; Jun Liu; Yanping Gong; Binjie Hu; Jianzhu Xie; Jin Cheng; Qian Huang (Diagnostics, 2024)
Background: Disseminated tumor cells (DTCs) are thought to be the initiators of tumor recurrence and metastasis. However, based on the current imaging examination methods, early detection of DTCs is extremely difficult due to their small number and dormant state. Methods: We used the SE-iFISH approach to detect bone marrow DTCs (mDTCs) in patients with breast or prostate cancer, and compared it with various imaging examination methods to explore its role in predicting metastasis and prognosis. Results: Fifteen patients were enrolled in this study. Among them, 11 patients showed imaging-confirmed bone metastases in different sites of the body, of which seven patients had iliac mDTCs and signs of iliac bone metastases on imaging. For the remaining four patients, imaging confirmed that the bone metastatic foci were far from the ilium, but in one patient, mDTCs were detected in the ilium. Interestedly, iliac mDTCs were also detected in two out of four patients who had no sign of bone metastases on imaging. Furthermore, the epithelial marker, CK18, was ubiquitously expressed in mDTCs, but its expression was very low in peripheral circulating tumor cells (pCTCs). The Kaplan–Meier plot suggested that CK18+ mDTCs ≥ 5 was related to poor overall survival (OS) compared with that of CK18+ mDTCs < 5 in breast cancer patients (median OS: 22.1 vs. 46.9 months; log-rank, p = 0.035). Conclusions: SE-iFISH examination for mDTCs is more sensitive than the conventional methods used for detecting bone metastases. mDTC detection facilitated the early finding of tumor cells in the bone marrow and ≥5 CK18+ mDTCs was associated with a poor prognosis in breast cancer patients.